From a Letter to President William Jewett Tucker - Tuck, Edward (Academy of Management Journal, 1959)
Presents the text of a letter given by Edward Tuck to President William Jewett Tucker of The Amos Tuck School at Darmouth College in Hanover, New Hampshire, about the school.